Analysis of the Impact of Study from Home on Adolescent during the Covid-19 Pandemic: Literature Review - Tiel, Devi Oktapia; Rahman, Subhannur; Rahmayani, Dini (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
The Covid-19 pandemic is an infectious disease that affects the performance of various sectors, one of which is the education sector. To deal with this, learning is made using the Study From Home method, namely an online learning system. This learning method has adaptations that are quite difficult to practice for adolescents, this is due to Study From Home having many obstacles in its implementation. This study uses a literature review study approach using sources based on predetermined criteria. The results of the journal, found the impact of Study From Home on adolescent mental health such as spending more time locking themselves in the room (psychosocial), adolescents who are stressed due to difficulty meeting their peers, changing lifestyle patterns of adolescents. So from these factors it can cause adolescents to experience a decrease in both interest in learning and achievement.